DIVERSITY OF SOIL SURFACE ARTHROPODS IN THE FOREST SURROUNDING BIOLOGY DEPARTMENT MANADO STATE UNIVERSITY - Billy Sampelan; Arrijani Arrijani; Utari Satiman (Universitas Negeri Manado, 2022)
Diversity in animals is a variation of the structure, shape, number, and other properties at a particular time and place. Diversity describes a situation that varies from one person to another, objects that occur cause differences in size, shape, texture, and amount. Arthropods are animals with segmented legs, and segments on the body belong to the animals that live both above and below the ground. This research aims to know the diversity and types of ground surface arthropods in the forest surrounding the Department of Biology, Faculty of Mathematics and Natural Science, Manado State University. This research is located in the forest area of the Department of Biology, Faculty of Mathematics and Natural Science, Universitas Negeri Manado, Tonsaru village, South Tondano District, Minahasa Regency, North Sulawesi. Taking data using the pitfall trap method and analyzing using Shannon Wiener diversity index, species richness index, species evenness index, and species dominance. The data collection and collection results obtained as many as 12 genera with a total of 166 individuals. Namely, Myrmica, Carebara, Paraponera, Papederinae, Anisolabis, Hogna, Spirostreptus, Cafius, Phalangium, Opilio, Oxidus, and Pholidoptera. The diversity index value yields 1,11043. The species richness index shows a value of 2,1518. Index the evenness of the species showed a value of 0,44687. The dominance of type indicates a value of 0,457. The level of diversity is moderate, species richness is low, evenness is moderate, and species dominance is low.